2017
DOI: 10.1007/s00167-017-4802-5
|View full text |Cite
|
Sign up to set email alerts
|

Microfracture is more cost-effective than autologous chondrocyte implantation: a review of level 1 and level 2 studies with 5 year follow-up

Abstract: PurposeFocal cartilage defects in the knee may have devastating effect on the knee joint, where two of the main surgical treatment options are microfracture and autologous chondrocyte implantation. Comparative studies have failed to establish which method yields the best clinical results. A cost-effectiveness analysis of microfracture and autologous chondrocyte implantation would contribute to the clinical decision process.MethodsA PubMed search identifying level I and level II studies with 5 year follow-up wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 49 publications
(93 reference statements)
2
63
0
2
Order By: Relevance
“…Cell-based scaffolds may be more advanced at the moment, but its high cost and time consumption means that it may not be economically feasible for all chondral defects to be treated in this manner. A study showed that although ACI has a slightly lower reoperation rate (12.1%) compared to microfracture (13.5%) after five years, microfracture is more cost-effective across all clinical outcomes due to its lower costs even when broader costs such as physiotherapies and work absences are included [13]. Similar studies comparing cell-free to cell-based scaffolds as well as other existing treatments are needed to determine cell-free scaffolds' cost-effectiveness and whether it can be incorporated within the clinical treatment pathway for chondral defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-based scaffolds may be more advanced at the moment, but its high cost and time consumption means that it may not be economically feasible for all chondral defects to be treated in this manner. A study showed that although ACI has a slightly lower reoperation rate (12.1%) compared to microfracture (13.5%) after five years, microfracture is more cost-effective across all clinical outcomes due to its lower costs even when broader costs such as physiotherapies and work absences are included [13]. Similar studies comparing cell-free to cell-based scaffolds as well as other existing treatments are needed to determine cell-free scaffolds' cost-effectiveness and whether it can be incorporated within the clinical treatment pathway for chondral defects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, cell-based techniques are costly and time-consuming as they require a two-step procedure: one to harvest chondrocytes and another to implant them. Biopsies taken to harvest chondrocytes also have the potential to cause donor-site morbidity [13]. Furthermore, the cartilage regenerated usually has limited mechanical properties [14], and a systematic review showed that ACI is not superior to microfracture or mosaicplasty for small defects [15].…”
Section: Introductionmentioning
confidence: 99%
“…The main methodological challenge was the lack of clinical data with which to inform any modelling or economic evaluation attempted. 12,14,18,20,22,24,25,27,28 In all these studies, the problem was (2018) 19 estimated the time at which long-term survivors would be considered effectively cured based on assumptions that were necessary to extrapolate the survival curve for trial participants. While disease modelling provides a way of estimating long-term effects, this does not substitute for good quality clinical trial evidence.…”
Section: Analysts' Resolution Of Methodological Challengesmentioning
confidence: 99%
“…Due to its minimally invasive procedure and low costs, MFx treatment is the most commonly used surgical cartilage repair technique. [39][40][41][42] MFx is used in patients with fullthickness cartilage lesions of the femoral condyles or the patellofemoral joint if the cartilage defect is < 2 to 3 cm 2 . In older patients and patients with a low demand, MFx can be used in cartilage defects > 3 cm.…”
Section: Microfracture Treatmentmentioning
confidence: 99%